Expression of the Extracellular Sulfatase SULF2 Affects Survival of Head and Neck Squamous Cell Carcinoma Patients - Yang, Yang; Ahn, Jaeil; Raghunathan, Rekha; Kallakury, Bhaskar V.; Davidson, Bruce; Kennedy, Zuzana Brnakova; Zaia, Joseph; Goldman, Radoslav (Frontiers in Oncology, 2021)
Sulfation of heparan sulfate proteoglycans (HSPG) regulates signaling of growth factor receptors via specific interactions with the sulfate groups. 6-O-Sulfation of HSPG is an impactful modification regulated by the activities of dedicated extracellular endosulfatases. Specifically, extracellular sulfatase Sulf-2 (SULF2) removes 6-O-sulfate from HS chains, modulates affinity of carrier HSPG to their ligands, and thereby influences activity of the downstream signaling pathway. In this study, we explored the effect of SULF2 expression on HSPG sulfation and its relationship to clinical outcomes of patients with head and neck squamous cell carcinoma (HNSCC). We found a significant overexpression of SULF2 in HNSCC tumor tissues which differs by tumor location and etiology. Expression of SULF2 mRNA from tumors associated with human papillomavirus (HPV) infection was 2-fold lower than in tumors associated with a history of tobacco and alcohol consumption. High SULF2 mRNA expression is significantly correlated with poor progression-free interval and overall survival of patient (n=499). Among all HS-related enzymes, SULF2 expression had the highest hazard ratio on overall survival after adjusting for clinical characteristics. SULF2 protein expression (n=124), determined by immunohistochemical analysis, showed a similar trend. The content of 6-O-sulfated HSPG, measured by staining with the HS3A8 antibody, was higher in adjacent mucosa compared to tumor tissue but revealed no difference based on SULF2 staining. LC-MS/MS analysis showed low abundance of N-sulfation and O-sulfation in HS but no significant difference between SULF2-positive and SULF2-negative tumors. Levels of enzymes modifying 6-O-sulfation, measured by RT-qPCR in HNSCC tumor tissues, suggests that HSPG sulfation is carried out by the co-regulated activities of multiple genes. Imbalance of the HS modifying enzymes in HNSCC tumors modifies the overall sulfation pattern, but the alteration of 6-O-sulfate is likely non-uniform and occurs in specific domains of the HS chains. These findings demonstrate that SULF2 expression correlates with survival of HNSCC patients and could potentially serve as a prognostic factor or target of therapeutic interventions.